Legend of the lost tomb - Corman, Julie; Winfrey, Jonathan (La Crosse Platinum Disc Corp., 2004)
In a daring adventure, teenagers Karen Lacey and John Robie, both 14, brave the forbidding Egyptian desert, seeking rescue John's archaeologist father, Dr. Erich Leonhardt, held prisoner by Dr. William Bent, his jealous rival. Bent tries to extort from Leonhardt the ancient papyrus map he has discovered and hidden. In Leonhardt's last journal entry, the youngsters find references linking the map to Ramses the Great. Karen, Leonhardt's summer intern, knows the legend that the pharaoh's soul walks the earth because the scarab covering his mummy's heart was stolen. If it were recovered, and found by the god Anubis to be light as a feather, Ramses would be allowed finally to pass over and join his father, the Sun God. The teenagers find the map and leave by train for the Elephantine Ruins, seeking the scarab as ransom for Leonhardt.
Brock Pierce, Kimberlee Peterson, Rick Rossovich and Stacy Keach.
Not suitable under 13 years.
Dolby digital.
In English.
Keywords: Feature films